Fixed dose drug combinations – are they pharmacoeconomically sound? Findings and implications especially for lower- and middle-income countries. (2nd January 2020) - Godman, Brian; McCabe, Holly; D Leong, Trudy; Mueller, Debjani; Martin, Antony P.; Hoxha, Iris; Mwita, Julius C.; Rwegerera, Godfrey Mutashambara; Massele, Amos; Costa, Juliana de Oliveira; do Nascimento, Renata Cristina Rezende Macedo; Lemos, Livia Lovato Pires de; et al.
ABSTRACT: Introduction: There are positive aspects regarding the prescribing of fixed dose combinations (FDCs) versus prescribing the medicines separately. However, these have to be balanced against concerns including increased costs and their irrationality in some cases. Consequently, there is a need to review their value among lower- and middle-income countries (LMICs) which have the greatest prevalence of both infectious and noninfectious diseases and issues of affordability. Areas covered: Review of potential advantages, disadvantages, cost-effectiveness, and availability of FDCs in high priority disease areas in LMICs and possible initiatives to enhance the prescribing of valued FDCs and limit their use where there are concerns with their value. Expert commentary: FDCs are valued across LMICs. Advantages include potentially improved response rates, reduced adverse reactions, increased adherence rates, and reduced costs. Concerns include increased chances of drug:drug interactions, reduced effectiveness, potential for imprecise diagnoses and higher unjustified prices. Overall certain FDCs including those for malaria, tuberculosis, and hypertension are valued and listed in the country's essential medicine lists, with initiatives needed to enhance their prescribing where currently low prescribing rates. Proposed initiatives include robust clinical and economic data to address the current paucity of pharmacoeconomic data. Irrational FDCs persists in some countries which are being addressed.